APPLICATION OF BASIC APPROACHES, TECHNOLOGIES AND CONCEPTS TO THE MANAGEMENT OF LOGISTICS AND SALES OF ENTERPRISES OF THE AGRICULTURAL COMPLEX - RYZHOVA, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The agro-industrial complex (APC) plays an important role in the economy, ensuring food security and the country’s export potential. In today’s conditions of competition and globalization, effective logistics and sales management are becoming critical for the success of agribusiness enterprises. The paper examines the main approaches and concepts to improve logistics processes and sales activities. It is noted that the choice of approach to logistics and sales management depends on the specific conditions and needs of the agribusiness enterprise. For enterprises of the agro-industrial complex, there is an urgent problem of introducing a logistic approach to increase the efficiency of economic activity and form a stable competitive position in the market of agricultural products. An uncontrolled sales process can lead a company to defeat in the struggle for survival in a market saturated with competitors’ products. In this regard, enterprises should seriously approach the organization and management of sales activities. Combining several concepts can provide the most effective solution to increase competitiveness, optimize costs, and meet market needs. Logistics technologies, which include various methods, tools, and systems, are analyzed to optimize and manage logistics processes. The connection of the main approaches and concepts to managing logistics and sales of enterprises of the agro-industrial complex was studied. In order to carry out a comparative analysis of the main concepts and approaches to logistics and sales management at the enterprises of the agro-industrial complex (APC), it is necessary to use such criteria as efficiency, costs, flexibility, complexity of implementation, integration with other business processes, as well as the impact on relations with customers and environmental friendliness Key aspects of various concepts and approaches are substantiated. Systematization of existing methodological approaches and concepts of logistics management of the sale of agricultural products has been carried out, the essence of which is the need to consider both the economic costs of agro-industrial production and the full effect of logistics costs. Implementing modern approaches and concepts allows agro-industrial complex enterprises to better adapt to market changes, ensuring sustainable development and increasing profitability.